One Master and Many End Users: Coordination Practices in Managing a Portfolio of Public Service Innovation Projects. (2nd July 2015) - Ambtman, Anouk den; van Riel, Allard C.R.; Lauche, Kristina; Hammedi, Wafa
Abstract: Managing a portfolio of interdependent innovation projects requires various forms of coordination. Coordination is important to mitigate risk and control resource utilization, but also to ensure that the end users experience the outcome of various innovation projects as integrated solutions to their needs. Simultaneously achieving control and user focused harmonisation in a project portfolio is not an easy task and may be hindered by organizational structures and coordination practices that focus on the internal division of labour and budgets rather than on taking a user perspective. In our case study in a public service organization we analyse the impact of the presence of one powerful stakeholder and anonymous and invisible end users on practices of coordinating a portfolio of service innovation projects.